“Blended” Education And The Transformation Of Teachers: A Long-Term Case Study In Postgraduate UK Higher Education - Motteram, Gary (Proceedings of the International Conference on Networked Learning, 2004)
This case study looks at the role of blended learning in language teacher education and focuses on the student experience of studying an element of a regular face-to-face class online. It shows how the experience is particularly relevant to in-service teachers who are following a master’s programme that equips them for implementing the use of educational technologies in their regular classroom. The paper explores a range of issues in the current adult education literature including deep and surface learning (Biggs, 1999), communities of practice (Wenger, 1998) and the importance of educational dialogue (Laurillard, 2002) and shows via the analysis of the data how important the blended nature of this course unit is for the teachers to get a balanced programme that upgrades skills and knowledge, but which also enables them to reflect on past and future practice. It shows how the five stage model of online communication (Salmon, 2000) can be a useful tool and that teachers can be transformed (Motteram and Teague, 2000).